Estudo químico e de atividade biológica de Paullinia elegans (Sapindaceae) - Guimarães, Rodrigo Nogueira (2006)
Paullinia elegans (Cambess.), known as "cipó-timbó", is found to occur in Brazil, Uruguay, Argentine and Paraguay. Chemical studies on this plant describes the isolation of cis-13-eicosenoic acid, cis-11-octadecenoic acid and 2,4-dihydroxy-3-methylenebutyronitrile from the seeds. Pharmacological studies showed the antiprotozoa activity against the epimastigote forms of Trypanosoma cruzi. In the present work we reported the phytochemical studies and antiinflammatory and antioxidant activities evaluation of the methanolic extract and its fractions from P. elegans (Ieaves). The ethanolic extract of P. elegans (leaves) was fractionated on column chromatography and purification of the fractions afforded a mixture of fatty esters(PE1), friedelanol (PE-2), oleanolic acid 3-O-acetyl(PE-3), a mixture of stigmasterol-3-O-β-D-glucopyranosil and sitosterol-3,7-O-α-glucopyranosil (PE-4a and PE-4b), kaempferol 3,7-0-a-dirhamnopyranoside (PE-5), canferol-3,O-raminosídeo (PE-6), calyptoterin glycosilated (PE-7) and 2-O-methyl-quiroinositol (PE-8). From the seeds was isolated cis-11-eicosenoic acid (PE-9). The structures of the isolated compounds were established by spectroscopic analysis, mainly 1D and 2D NMR, and comparison with literature data. The assays for antioxidant activities were performed by using the DPPH method. The anti-inflammatory activities were evaluated on ear edema induced by croton oil in rats.